Supply Chain Strategy in Modernization of State Support Instruments for Small Farms in Ukraine - Olga M, Varchenko; Dmytro F, Krysanov; Olena V, Shubravska; Larysa P, Khakhula; Olecya Y, Gavryk; Valentyna A, Byba; Inna V, Honcharuk (International Journal of Supply Chain Management, 2020)
Abstract- Sustainable food value chains can offer important pathways out of poverty for the millions of small farms in developing countries. The need to concentrate state support for the development of small farms is proved in the article. The results of the cluster analysis of small farms show that it is advisable to send state support to the development of farms in which revenues are generated from the sale of crop products, as well as from other crop products -